2020
DOI: 10.7759/cureus.7188
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index and Diet with Symptomatic Gall Stone Disease: A Case-Control Study

Abstract: Background: Gall stone disease (GSD) is one of the commonest gastrointestinal disorders. Causative factors can be non-modifiable as genetics and modifiable like dietary habits. High-fat diet and high BMI are well known contributing factors world-over. Local and regional data is deficient about these factors. Moreover, Indo-Pakistani dietary patterns are very different from the western population. This study was conducted to see the association of high BMI and diet with GSD in our population.Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Lastly, oily fish consumption was associated with a reduced risk of cholelithiasis, in line with previous observational studies highlighting the protective effect of oily fish consumption ( 25 , 26 ). The exact mechanism by which oily fish reduces the risk of cholelithiasis remains uncertain, but it may be related to its high fat content, potentially influencing bile acids and cholesterol levels in the bile, thereby reducing gallstone formation.…”
Section: Discussionsupporting
confidence: 90%
“…Lastly, oily fish consumption was associated with a reduced risk of cholelithiasis, in line with previous observational studies highlighting the protective effect of oily fish consumption ( 25 , 26 ). The exact mechanism by which oily fish reduces the risk of cholelithiasis remains uncertain, but it may be related to its high fat content, potentially influencing bile acids and cholesterol levels in the bile, thereby reducing gallstone formation.…”
Section: Discussionsupporting
confidence: 90%
“…As a rule, the “western diet” increases biliary secretion of bile acids and reshapes the gut microbiota in obesity by increasing the Firmicutes and decreasing the Bacteroidetes [ 35 , 62 ]. Several population-based studies have shown that populations given increased amounts of polyunsaturated fats have a significant risk of developing gallstones [ 9 , 12 , 132 , 133 , 134 ]. The MICOL study, however, showed no such association [ 135 ].…”
Section: Some Reasons For the Lack Of Unity In The Assessment Of Tmentioning
confidence: 99%
“…), social and economic issues, fertility, and intestinal factors (with increased absorption of cholesterol, slow intestinal motility, and dysbiosis) [ 7 , 8 , 9 , 10 ]. Obesity is a major risk factor for developing GSD [ 9 , 10 , 11 , 12 ] because it is accompanied by increased synthesis and excretion of cholesterol into bile [ 13 ], wherein the amount of cholesterol produced is directly proportional to being overweight [ 11 ].Obesity is regarded as an inflammatory condition [ 14 ]. Inflammation may be the potential link between insulin resistance and gallstones [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar incidences are reported in other studies as well 9 , 12 . Earlier studies have found an increase rate of complications and conversion in patients with a higher BMI 13 , 14 . Few population-based studies have associated diabetes with an increased risk of gall stones and postoperative complications 15 .…”
Section: Discussionmentioning
confidence: 85%